SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SUBKON-TRAKTOR MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCES (AHP) - Devi wulandari (Yayasan Pendidikan Cahaya Budaya Indonesia, 2024)
Subcontractor selection is a crucial factor in the success of a construction project. Mistakes in selecting subcontractors can lead to project delays, increased costs, and decreased work quality. This study aims to develop a Decision Support System (DSS) for subcontractor selection using the Analytic Hierarchy Process (AHP) method. This method is used to determine criteria weights and rank alternative subcontractors. The criteria used include price, quality, experience, completion time, and reputation. The results show that the AHP method is capable of providing objective and structured recommendations for the best subcontractors.